Evaluation of the safety, tolerability, pharmacokinetics and pharmacodynamics of SM17 in healthy volunteers: results from pre-clinical models and a first-in-human, randomized, double blinded clinical trial - Xu, Guolin; Paglialunga, Sabina; Qian, Xuchen; Ding, Ru; Webster, Kenneth; van Haarst, Aernout; Engel, Caroline; Hui, Chin Wai; Lam, Lik Hang; Li, Weimin; Wu, Wai Chung; Rasmussen, Scott; et al. (Frontiers in Immunology, 2024)
BackgroundAlarmins mediate type 2 T helper cell (Th2) inflammation and serve as upstream signaling elements in allergic inflammation and autoimmune responses. The alarmin interleukin (IL)-25 binds to a multi-domain receptor consisting of IL-17RA and IL-17RB subunits, resulting in the release of Th2 cytokines IL-4, IL-5, IL-9 and IL-13 to drive an inflammatory response. Therefore, the blockage of IL-17RB via SM17, a novel humanized monoclonal antibody, offers an attractive therapeutic target for Th2-mediated diseases, such as asthma.MethodsWild-type mice were stimulated with house dust mite (HDM) extracts for evaluation of SM17’s pre-clinical efficacy in allergic asthma. The safety, pharmacokinectics (PK), pharmacodynamics (PD), and immunogenicity of intravenous (IV) doses of SM17 were assessed in a 2-part clinical study in healthy adult subjects. In Part A, 53 healthy participants were enrolled to receive a single IV dose of SM17 (2, 20, 70, 200, 400, 600, 1200 mg) or placebo. In Part B, 24 healthy subjects were enrolled to receive a single IV dose of SM17 every two weeks (Q2W; 200, 400, 600 mg) or placebo for a total of 3 doses.ResultsAnimal studies demonstrated that SM17 significantly suppressed Th2 inflammation in the bronchoalveolar lavage fluid and infiltration of immune cells into the lungs. In the Phase I clinical study, no drug-related serious adverse events were observed. Total SM17 exposure increased by approximately 60- to 188-fold with a 60-fold increase in dose from 20 to 1200 mg SM17. Upon administration of the third dose, mean accumulation ratios over 200-600 mg was 1.5 to 2.1, which confirms moderate accumulation of SM17. After Q2W dosing of SM17 over 4 weeks, total exposure increased in a dose-proportional manner from 200 mg to 600 mg SM17.ConclusionIn the pre-clinical studies, we demonstrated that SM17 is a potential therapeutic agent to treat allergic asthma. In the Phase 1 clinical trial, a single IV dose of SM17 up to 1200 mg and three Q2W doses up to 600 mg were well tolerated in healthy participants and demonstrated a favorable safety profile. The pre-clinical efficacy and clinical PK and immunogenicity results of SM17 support further clinical development.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT05332834.